Analysis Of Internal Factors Affecting the Net Interest Margin of Conventional National Private Banks - Cundo Harimurti (Majalah Ilmiah Bijak, 2022)
This study analyses the influence of size, capital adequacy ratio, Operating Costs and Operating Income, Loan to Deposit Ratio, and Loan to Asset Ratio on the Net Interest Margin of Conventional National Private Banks. The sample in this study is 37 conventional national private banks based on Indonesia Banking Statistics 2021. Data analysis with multiple linear regression analysis with secondary data during 2012-2021. The results of the study found that size has a significant negative effect on Net Interest Margin. The capital adequacy ratio has a significant positive impact on Net Interest Margin. Operating Expenses and Operating Income have an insignificant effect on Net Interest Margin. Loan to Deposit Ratio has a significant positive impact on Net Interest Margin. Loan to Asset Ratio has a significant positive effect on Net Interest Margin.